2006
DOI: 10.1369/jhc.6a7058.2007
|View full text |Cite
|
Sign up to set email alerts
|

Nestin Expression in Adult and Developing Human Kidney

Abstract: S U M M A R Y Nestin is considered a marker of neurogenic and myogenic precursor cells. Its arrangement is regulated by cyclin-dependent kinase 5 (CDK5), which is expressed in murine podocytes. We investigated nestin expression in human adult and fetal kidney as well as CDK5 presence in adult human podocytes. Confocal microscopy demonstrated that adult glomeruli display nestin immunoreactivity in vimentin-expressing cells with the podocyte morphology and not in cells bearing the endothelial marker CD31. Glomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
26
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 65 publications
7
26
0
1
Order By: Relevance
“…Liu et al [17] also showed that the degree of albuminuria in diabetic rats was negatively correlated with the Nestin concentration and positively correlated with the CDK5 level. Roscovitine could reduce the degradation of NestinNestin and ameliorate podocyte injuries [18, 19]. Thus, our findings indicate that the protective role of Nestin on podocytes is mediated by inhibition of the kinase activity of CDK5 when challenged by Ang II.…”
Section: Discussionmentioning
confidence: 74%
“…Liu et al [17] also showed that the degree of albuminuria in diabetic rats was negatively correlated with the Nestin concentration and positively correlated with the CDK5 level. Roscovitine could reduce the degradation of NestinNestin and ameliorate podocyte injuries [18, 19]. Thus, our findings indicate that the protective role of Nestin on podocytes is mediated by inhibition of the kinase activity of CDK5 when challenged by Ang II.…”
Section: Discussionmentioning
confidence: 74%
“…Nestin expression has recently been documented in rat, 13 mouse, 14 and human 11,15 kidney, where expression in mature kidney is limited to podocytes. We have found that nestin ex- pression in normal mature human glomeruli is confined to podocytes and that nestin expression persists in podocytes in every glomerular disease studied.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that nestin is expressed in human podocytes in normal kidney and all glomerular diseases studied to date. 11 Nestin is an intermediate filament protein that is genetically distinct from other intermediate filaments and was originally identified in neural progenitor cells, 12 but only recently, it has been found that nestin is expressed in rat, 13 mouse, 14 and human 11,15 podocytes. We reasoned that nestin might serve as a robust marker for podocytes, and we have carried out a study of nestin expression in crescentic disease, with the goal of assessing the podocyte contribution to crescents.…”
mentioning
confidence: 99%
“…Subsequently, due to improving detection methods, nestin expression was described in many other embryonic or fetal tissues, e.g. the presomitic mesoderm [Zimmerman et al, 1994], mesonephric mesenchyme [Fröjdman et al, 1997], developing cardiomyocytes [Kachinski et al, 1995], endothelium in developing blood vessels [Mokrý and Němeček, 1998a;Mokrý et al, 2004], maturing teeth [Terling et al, 1995], lens cells in the developing eye [Mokrý and Němeček, 1998b;Yang et al, 2000], and differentiating podocytes of the kidney [Bertelli et al, 2007], etc. One of the most characteristic features of nestin is its reexpression in situations that reproduce developmental phases.…”
Section: Discussionmentioning
confidence: 99%